2020
DOI: 10.1097/scs.0000000000006372
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Intracranial Volume With Head Surface Volume in Patients With Multisutural Craniosynostosis

Abstract: Intracranial volume (ICV) is an important parameter for monitoring patients with multisutural craniosynostosis. Intracranial volume measurements are routinely derived from computed tomography (CT) head scans, which involves ionizing radiation. Estimation of ICV from head surface volumes could prove useful as 3D surface scanners could be used to indirectly acquire ICV information, using a non-invasive, non-ionizing method. Pre-and postoperative 3D CT scans from spring-assisted posterior vault expansion (sPVE) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It also allows some correction of a brachycephalic skull shape. At Great Ormond Street Hospital for Children (GOSH), the procedure of choice is a spring-assisted posterior vault expansion (sPVE) [ 10 ]. It is a less invasive operation than a fronto-orbital reconstruction, providing a greater degree of vault expansion [ 11 ] and leaving the frontal region intact for any subsequent fronto-facial surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It also allows some correction of a brachycephalic skull shape. At Great Ormond Street Hospital for Children (GOSH), the procedure of choice is a spring-assisted posterior vault expansion (sPVE) [ 10 ]. It is a less invasive operation than a fronto-orbital reconstruction, providing a greater degree of vault expansion [ 11 ] and leaving the frontal region intact for any subsequent fronto-facial surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this work included a relatively small population, due to the limited number of patients who had both pre- and postoperative CT scans available at GOSH. A recent study from our group 25 , showed that the ICV in syndromic patients correlates with the head surface volume. Therefore, in perspective works, non-ionizing imaging methods such as 3D surface scanning could be used to perform both preoperative planning and postoperative assessment and overcome the need for CT data in the modelling pipeline.…”
Section: Discussionmentioning
confidence: 81%
“…A small cohort of patients was included in this study, due to the limited number of patients who had both pre-and postoperative CT scans available at our Centre. A recent study from our group has shown that ICV in SC patients correlates well with head surface volume (Ramdat Misier et al, 2020): in the future, both preoperative planning and post-operative assessment could be performed by means of nonionizing imaging methods such as 3D surface scanning (Ramdat Misier et al, 2020), thus overcoming the need for CT data in the modelling pipeline.…”
Section: Tablementioning
confidence: 99%